The Promise of Kiruna’s Iron Ore in the Swedish Imagination, c. 1901–1915 - Roberts, Peder (Journal of Northern Studies, 2020)
Iron ore mining in the Norrbotten region of Sweden began in the early years of the twentieth century as a commercially uncertain and even dangerous proposition. But even before it began to generate profits, public debate began over the appropriate role of the state and of private capital (including foreign investors). This included whether iron ore should be exported for profit or retained for future processing in Sweden—even though the technology and infrastructure for such domestic industry did not exist. Tracing the evolution of this debate in the Swedish news media through to the First World War, this paper argues that the revenue generated by exports became more attractive than the promise of future domestic industry because that revenue could underwrite pressing political objectives. Although domestic iron ore processing remained linked to visions of future industrial prosperity, uncertain visions of future prosperity lost appeal as the capacity for export revenues to generate prosperity in the present became more potent.